Dinamika Pemilihan Kepala Desa: (Studi Konflik Sosial yang Muncul Pasca Pemilihan) - Dules Ery Pratama Harahap; Murniwati Lase; Julia Ivanna (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Village Head Election (Pilkades) is a form of local democracy that serves as a forum for community participation in determining leaders at the village level. However, behind this democratic process, social dynamics often emerge that lead to conflict between residents. This study aims to examine the forms, causes, and impacts of social conflict that occurred after the village head election. Using a qualitative-descriptive approach, data were collected through in-depth interviews, observations, and documentation studies in one of the villages that experienced conflict after the Pilkades. The results of the study show that the conflict was generally triggered by dissatisfaction with the election results, allegations of fraud, and rivalry between groups supporting candidates. This conflict has an impact on disrupting social harmony, decreasing community participation in village activities, and the emergence of social segregation. This study emphasizes the importance of an effective dispute resolution mechanism, the neutrality of the election committee, and the active role of community leaders in reducing potential conflict. These findings are expected to provide input for Pilkades organizers and related parties in creating a peaceful and constructive election process.